Clean water self-sufficiency and well water filtration method education for health workers in gowa regency - Ella Andayanie; Alfina Baharuddin; Asmarani Harma; Annisa Junaid; Yuliati; Suharni A. Fachrin (Abdimas Polsaka, 2025)
The quality of well water in Jenemadingi hamlet does not meet health standards. As a result, cases of diarrhea and stunting are also high. The purpose of this community service is to provide training in water purification techniques. This educational method is carried out in five stages: the socialisation stage and the implementation stage. This activity comprises three sessions: the first stage, which includes a pre-test administered through a questionnaire, utilising lecture, question-and-answer, and discussion methods; the post-test and evaluation of post-test results; the technology implementation stage; the monitoring and evaluation stage; and the program sustainability stage. The results of the community service activity indicate that the socialization of clean water and sanitation education is beneficial for the community, as the community's knowledge has significantly improved. The average score increased from 20.22 in the pre-test to 23.18 in the post-test, with a p-value of 0.001, indicating a significant difference. These results confirm the effectiveness of the clean water and sanitation education program